Modal gain and time-resolved photoluminescence of Ga(NAsP) heterostructures pseudomorphically grown on Silicon (001) substrate - Gerhardt, Nils Christopher; Hofmann, Martin R.; Koukourakis, Nektarios; Funke, Dominic A.; Kunert, B.; Liebich, S.; Trusheim, D.; Zimprich, M.; Bückers, C.; Koch, S. W.; Volz, K.; Stolz, W.

Modal gain and time-resolved photoluminescence of Ga(NAsP) heterostructures pseudomorphically grown on silicon (001) substrate - Gerhardt, Nils Christopher; Hofmann, Martin R.; Koukourakis, Nektarios; Funke, Dominic A.; Kunert, B.; Liebich, S.; Trusheim, D.; Zimprich, M.; Bückers, C.; Koch, S. W.; Volz, K.; Stolz, W.

Wie das Kollegium zur Zusammenarbeit angeregt werden kann? Schulleitungshandeln und Lehrerkooperation - Harazd, B.; Drossel, Kerstin (Schulverwaltung. Nordrhein-Westfalen)

Quantitative photoacoustic blood oxygenation measurement of whole porcine blood samples using a multi-wavelength semiconductor laser system - Friedrich, Claus-Stefan; Mienkina, Martin; Gerhardt, Nils Christopher; Beckmann, Martin; Schmitz, Georg; Hofmann, Martin R.; Brenner, Carsten; Jörger, Manfred; Strauß, Andreas (Diffuse optical imaging III)

Photorefractive two-wave mixing for image amplification in digital holography - Koukourakis, Nektarios; Li, Mingyuan; Lai, Ryan Yiu Wai; Brenner, Carsten; Gerhardt, Nils Christopher; Hofmann, Martin; Abdelwahab, Tarek; Höpfner, Henning; Darakis, Emmanouil (Optics express)

Experimental evaluation of multispectral photoacoustic coded excitation using orthogonal unipolar golay codes - Mienkina, Martin; Friedrich, Claus-Stefan; Gerhardt, Nils Christopher; Hofmann, Martin; Schmitz, Georg; Eder, Alexander (442. Wilhelm und Else Heraeus-Seminar "Molecular Imaging" in Bad Honnef, October 5th - 8th, 2009)

Modal gain and time-resolved photoluminescence of Ga(NAsP) heterostructures pseudomorphically grown on silicon (001) substrate - Gerhardt, Nils Christopher; Hofmann, Martin R.; Koukourakis, Nektarios; Funke, Dominic A.; Kunert, B.; Liebich, S.; Trusheim, D.; Zimprich, M.; Bückers, C.; Koch, S. W.; Volz, K.; Stolz, W.

Quantitative photoacoustic blood oxygenation measurement of whole porcine blood samples using a multi-wavelength semiconductor laser system - Brenner, Carsten; Gerhardt, Nils Christopher; Hofmann, Martin R.; Schmitz, Georg; Friedrich, Claus-Stefan; Mienkina, Martin P.; Beckmann, Martin F.; Jörger, Manfred; Strauß, Andreas

Modal gain and time-resolved photoluminescence of Ga(NAsP) heterostructures pseudomorphically grown on silicon (001) substrate - Gerhardt, Nils Christopher; Hofmann, Martin R.; Koukourakis, Nektarios; Funke, Dominic A.; Kunert, B.; Liebich, S.; Trusheim, D.; Zimprich, M.; Buckers, C.; Koch, S. W.; Volz, K.; Stolz, W.

Spectroscopic optical coherence tomography for substance identification - Gerhardt, Nils Christopher; Hofmann, Martin R.; Jaedicke, Volker; Kasseck, Christoph; Wiethoff, Helge; Agcaer, Semih; Welp, Hubert

Application of the Discontinuous Galerkin Time Domain Method to the Optics of Bi-Chiral Plasmonic Crystals - Grynko, Yevgen; Förstner, Jens; Meier, Torsten; Radke, André; Gissibl, Timo; Braun, Paul V.; Giessen, Harald
A simulation environment for metallic nanostructures based on the Discontinuous Galerkin Time Domain method is presented. It is used to model optical transmission by silver bi‐chiral plasmonic crystals. The results of simulations qualitatively and quantitavely agree with experimental measurements of transmitted circular polarization.
Keywords: tet_topic_meta

Ultrafast spin-induced polarization oscillations with tunable lifetime in vertical-cavity surface-emitting lasers - Gerhardt, N. C.; Li, M. Y.; Jähme, H.; Höpfner, H.; Ackemann, T.; Hofmann, M. R. (Applied Physics Letters)
We report spin-induced polarization oscillations in vertical-cavity surface-emitting lasers above threshold and at room temperature. The oscillation frequency is 11.6 GHz, which is significantly higher than the modulation bandwidth of less than 4 GHz in the device. The oscillation frequency is determined by an additional resonance frequency in birefringence containing microcavities, which is potentially much higher than the conventional relaxation oscillation frequency. The damping of the oscillations can be controlled by the current, allowing for oscillation lifetimes much longer than the spin lifetime in the device as well as for short bursts potentially interesting for information transmission.

Utilizing an Analytical Approximation for c44E to Enhance the Inverse Method for Material Parameter Identification of Piezoceramics - Rautenberg, Jens; Rupitsch, Stefan J.; Henning, Bernd; Lerch, Reinhard (7th International Workshop on Direct and Inverse Problems in Piezoelectricity)
There has been a lot of progress in finding measurable quantities of high in- formation content for the inverse determination of piezoelectric material properties. Since some material parameters (mainly \textgreek{e}S 11, e15and cE 44) do not or only marginally influence the electrical impedance over frequency, it is not sufficient to look only at the electri- cal impedance of discoidal piezoceramics [1]. Moreover, the parameter sensitivities vary with respect to the diameter-thickness ratio of the disc and the design of an ultrasonic transducer's piezoceramic has to match other requirements than those of a good material characterization [2, 3]. That is why it is still desirable to find model based approaches for parameter identification that either keep the technical effort low (e.g., only an impedance measurement) or increase speed of the inversion procedure. In this contribution we answer the question if an additional analytical approximation of cE 44, strictly following the ideas of Theocaris [4], in conjunction with a single measured elec- trical impedance will be sufficient for an accurate simulation of both, electrical impedance and surface normal velocity of a piezoceramic disc. Thereby, the remaining parameters are identified by means of the Inverse Method. Furthermore, we use the parameter ap- proximation as an initial guess and limiting boundary to speed up the inverse algorithm if both, electrical impedance and surface normal velocity are taken into account within the optimization procedure.

Birefringence and spin controlled ultrafast polarization oscillations in vertical-cavity surface-emitting lasers - Li, Mingyuan; Jähme, Hendrik; Soldat, Henning; Gerhardt, Nils Christopher; Hofmann, Martin; Ackemann, Thorsten (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference (CLEO Europe/EQEC 2011))

Direct limits of infinite-dimensional Lie groups - Glöckner, Helge (Developments and trends in infinite-dimensional Lie theory)
Keywords: 22E65; 22E15; 46A13; 46T05; 54D50

Direct limit constructions in infinite dimensional Lie theory - Dahmen, Rafael

Phosphonium Salt Catalyzed Addition of Diethylzinc to Aldehydes - Werner, Thomas; Riahi, Abdol; Schramm, Heiko (Synthesis)
Keywords: T2

Interaction of phase‐transformations and plasticity – a multi‐phase micro‐sphere approach - Ostwald, Richard; Bartel, Thorsten; Menzel, Andreas (PAMM)
Abstract We present an efficient model for the simulation of solid to solid phase‐transformations in polycrystalline materials. As a basis, we implement a scalar‐valued Gibbs‐energy‐barrier‐based phase‐transformation model making use of statistical physics. In this work, we particularly adopt the model for the simulation of phase‐transformations between an austenitic parent phase and a martensitic tension and compression phase. The incorporation of plasticity phenomena is established by enhancing the Helmholtz free energy functions of the material phases considered, where the plastic driving forces acting in each phase are derived from the overall free energy potential. The coupled model is embedded into a micro‐sphere formulation in order to simulate three‐dimensional boundary value problems—a technique well‐established in the context of computational inelasticity at small strains. It is shown that the model is capable of reflecting experimentally observed behaviour. (© 2011 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)

Experimental and Computational Investigation of Machining Processes for Functionally Graded Materials - Biermann, D.; Menzel, A.; Bartel, T.; Höhne, F.; Holtermann, R.; Ostwald, Richard; Sieben, B.; Tiffe, M.; Zabel, A. (Procedia Engineering)

Preserving Charge and Oxidation State of Au(III) Ions in an Agent-Functionalized Nanocrystal Model System - Müllegger, Stefan; Schöfberger, Wolfgang; Rashidi, Mohammad; Lengauer, Thomas; Klappenberger, Florian; Diller, Katharina; Kara, Kamuran; Barth, Johannes V.; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold (ACS Nano)